Posición postural y su influencia en el desarrollo de lumbalgias en secretarias de 35 a 45 años del municipio. Cantón Buena Fe. Periodo septiembre 2017 a febrero 2018. - Vélez Iza, Amanda Zulay (2018)
Through the programmed research activity, we sought to analyze the influence of the postural position in the development of lumbago in secretaries from 35 to 45 years of age, who work in the Municipality of the Canton Buena Fe, to achieve this goal method were selected. theoretical and empirical, which served as the basis for the collection and subsequent analysis of the required information. The operative development of the investigation was verified in two stages, in the first the occurrence and incidence of low back pain was diagnosed in the secretaries under study, in the second after processed the derived data bases, the system of actions was elaborated consequently proposed to solve the assumed scientific problem, in turn through the application of the selected methods and techniques, it was concluded that the postural position adopted by the secretaries had a significant influence on the pathology under study, for which reason the expected work hypothesis. It is the criterion of this author that, if both the conclusions and the recommendations reached are taken into account, it would significantly improve the quality of life of the secretaries, as well as their contributions to the work carried out, precisely in the aforementioned the feasibility and importance of the content of the final report presented.